An effective and ecofriendly suggestion to decrease atmospheric carbon dioxide by using NH3 gas - H. Eryilmaz (Global Journal of Environmental Science and Management)
Global warming is increasing permanently, because the concentration of CO2 in the atmosphere is rising continuously. According to National Oceanographic and Atmospheric Administration, the concentration of CO2 in the atmosphere was 407 ppm in June 2016 and 413 ppm in April 2017 as a last record for now. If the effects of other greenhouse gases, such as CH4, N2O, SF6, NF3, chlorofluorocarbons, hydrofluorocarbons, perfluorocarbons are added, the effective concentration may reach or exceed 550 ppm CO2-equivalent.  According to the United Nations Intergovernmental Panel on Climate Change-2014 Climate Change Report, this is about two times higher than 278 ppm CO2 concentration in the pre-industrial year 1765. Thus, very urgent solutions must be found. The aim of this article is to suggest a vital, fast and very meticulous solution using NH3 gas in the atmosphere in order to decrease the atmospheric CO2 without delay. The laboratory experiments in the gas phase for (NH3+ CO2) reaction showed us that to use NH3 gas in the atmosphere will be a very fast, effective method for decreasing CO2 concentration of atmosphere.  (NH3+ CO2) reaction is also quantitative in the cold atmosphere strata and there will be no more free ammonia in the atmosphere and no public health problem.